Illusion of linearity in geometry: Effect in multiple-choice problems - Vlahović-Štetić, Vesna (Array, 2010)
The aim of this study was to examine if there is a difference in the performance on non-linear problems regarding age, gender, and solving situation, and whether the multiple-choice answer format influences students' thinking. A total of 112 students, aged 15-16 and 18-19, were asked to solve problems for which solutions based on proportionality were appropriate and others that were not, presented in multiple-choice format. One group of students solved non-linear problems that had an incorrect linear solution among five offered answers, and the other group solved non-linear problems that didn't have a linear solution among offered answers. Both groups also solved linear problems. All students solved linear problems very successfully. Older students' performance on non-linear problems was better than younger students' performance and the interaction between age and solving situation was also significant. There were no gender differences. The effect of solving situation was also significant. Students who didn't have an offered linear solution were more successful than students with offered linear solution in multiple-choice items. Students' solving methods underlying incorrect answers were also analyzed as well as how much they used drawing in the solving of problems.